Pre-clinical assays predict pan-African Echis viper efficacy for a species-specific antivenom. - Nicholas R Casewell; Darren A N Cook; Simon C Wagstaff; Abdulsalami Nasidi; Nandul Durfa; Wolfgang Wüster; Robert A Harrison (Public Library of Science (PLoS), 2010)
Snakebite is a significant cause of death and disability in subsistent farming populations of sub-Saharan Africa. Antivenom is the most effective treatment of envenoming and is manufactured from IgG of venom-immunised horses/sheep but, because of complex fiscal reasons, there is a paucity of antivenom in sub-Saharan Africa. To address the plight of thousands of snakebite victims in savannah Nigeria, the EchiTAb Study Group organised the production, testing and delivery of antivenoms designed to treat envenoming by the most medically-important snakes in the region. The Echis saw-scaled vipers have a wide African distribution and medical importance. In an effort to maximise the clinical utility of scarce antivenom resources in Africa, we aimed to ascertain, at the pre-clinical level, to what extent the E. ocellatus-specific EchiTAbG antivenom, which was designed specifically for Nigeria, neutralised the lethal activity of venom from two other African species, E. pyramidum leakeyi and E. coloratus.Despite apparently quite distinctive venom protein profiles, we observed extensive cross-species similarity in the immuno-reactivity profiles of Echis species-specific antisera. Using WHO standard pre-clinical in vivo tests, we determined that the monospecific EchiTAbG antivenom was as effective at neutralising the venom-induced lethal effects of E. pyramidum leakeyi and E. coloratus as it was against E. ocellatus venom. Under the restricted conditions of this assay, the antivenom was ineffective against the lethal effects of venom from the non-African Echis species, E. carinatus sochureki.Using WHO-recommended pre-clinical tests we have demonstrated that the new anti-E. ocellatus monospecific antivenom EchiTAbG, developed in response to the considerable snakebite-induced mortality and morbidity in Nigeria, neutralised the lethal effects of venoms from Echis species representing each taxonomic group of this genus in Africa. This suggests that this monospecific antivenom has potential to treat envenoming by most, perhaps all, African Echis species.